Georg Brandes' billeder - Dahlerup, Pil (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
NB: Artiklen er på dansk, kun resuméet er på engelsk. Pil Dahlerup: Georg Brandes’ pictures Georg Brandes’ interest for the visual arts is well-known but has not been subject to any closer studies. In this article, the young Georg Brandes’ relation to visual arts in the period of 1860-1866 is examined on the basis of published and unpublished texts from his hand including his diaries and letters. The emphasis is laid on his interest in sculpture, the art of painting and photography. While at the same being busily engaged in his studies – firstly law, later aesthetics – he visited with his friend Julius Lange, who would later become a well-known art historian, all Danish exhibitions and museums in Copenhagen and acquired an in-depth knowledge of the painters and sculptors of the time. Foreign artists were studied by the two friends through Julius Lange’s photographs. It is interesting per se to see this side of Georg Brandes’ personality unfolded. At the same time, it can be proven that it was the visual arts and in particular the portrait painting and the genre painting that sparked Georg Brandes’ development from idealism to realism. And that is not all. To the young Georg Brandes the visual arts offered richer modes of expression than literature, and he tried to transfer the sensuousness of the visual arts to the verbal arts. Thus, he contributed to The Visual Turn in the second half of the century, i.e. the development that turned vision into the dominant sense and the picture into the dominant medium.